Pengembangan Instrumen Penilaian Karakter dan Keterampilan Proses dalam Pembelajaran - Yitra Gloria Bana; Selviana Ambu Kaka; Roimanson Panjaitan (Jurnal Ilmiah Literasi Indonesia, 2026)
This study aims to examine in depth the development of character and process skills assessment instruments in learning through a library research approach. The study was conducted by synthesizing various reputable literature sources, including textbooks, indexed scientific journals, and relevant education policy documents. The results show that a good character assessment instrument must measure three dimensions of character comprehensively, namely moral knowing, moral feeling, and moral action, using assessment rubrics with clear behavioral descriptors. Effective process skills assessment instruments take the form of performance assessments that authentically record students’ abilities to observe, question, collect information, reason, and communicate. The development of both instruments must meet content validity, internal reliability, and practical usability criteria to be truly useful for teachers in implementing the Merdeka Curriculum.